Ethnic influence on nonalcoholic fatty liver disease prevalence and lack of disease awareness in the United States, 2011–2016. (4th March 2020) - Le, M. H.; Yeo, Y. H.; Cheung, R.; Wong, V. W.-S.; Nguyen, M. H.
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is a rising global disease associated with clinical and economic burdens. Objectives: We aimed to quantify NAFLD prevalence and awareness to provide stakeholders necessary information to combat NAFLD burden. Methods: This study utilizes data from the National Health and Nutrition Examination Survey 2011–2016 and included 4538 adult participants who did not have heavy drinking or viral hepatitis history. The US fatty liver index defined NAFLD and NAFLD fibrosis score defined fibrosis. NAFLD awareness was captured by questionnaire. Results: Amongst the study population of 4538 persons, NAFLD prevalence was 32.5%, lowest in non‐Hispanic Blacks (18.0%) and Asians (18.1%), highest amongst Mexican Americans (48.4%). Within the NAFLD group, advanced fibrosis was highest in non‐Hispanic Blacks (28.5%) and lowest amongst non‐Hispanic Asians (2.7%). Of the 1473 (97.5%) NAFLD participants who answered NAFLD awareness question, 90% visited a healthcare centre at least once in the past year, but only 5.1% were aware of having NAFLD. On weighted population estimates, 77.33 million persons had NAFLD, 17.63 million had advanced fibrosis, and 73.39 million NAFLD participants were not aware of having NAFLD. Conclusions: Of 77.33 million people in the United States have NAFLD with 17.63 million having advanced fibrosis, with lowest prevalence in non‐Hispanic Asians and highest in Mexican Americans. A conundrum exists amongst non‐Hispanic Blacks who have low NAFLD prevalence but highest prevalence of advanced fibrosis. Awareness of NAFLD was low across all ethnicities. Effort is needed to improve disease awareness whilst addressing NAFLD clinical burden across ethnicities. Abstract :